Effect of rifampin and bacitracin on nasal carriers of Staphylococcus aureus. - McAnally, T P (1984)
Anterior nares cultures from 664 hospital personnel identified 165 (24.8%) as carriers of Staphylococcus aureus. Persistent carriers (17.8%) were identified and randomly assigned to one of four treatment groups: rifampin (600 mg once a day for 5 days), bacitracin ointment (topically applied three times a day for 10 days), combined rifampin and bacitracin, and control (no treatment). Bacitracin ointment was ineffective in eliminating S. aureus from the anterior nares and had a postreatment carrier rate equal to the control rate. Rifampin therapy caused a highly significant reduction (79%) in carriage; however, combined therapy was not as effective as treatment with rifampin alone. Of 132 strains of staphylococci isolated before and after treatment, all were susceptible to less than 0.016 micrograms of rifampin per ml. This study demonstrates that rifampin may be an effective antistaphylococcal antibiotic and could be used to control the carrier state in high-risk situations.